2014
DOI: 10.1371/journal.pone.0096625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression Analysis of ATP-Gated P2X7 Receptor Involved in Japanese Flounder (Paralichthys olivaceus) Innate Immune Response

Abstract: ATP-gated P2X7 receptor (P2RX7) channel is a key component for purinergic signaling and plays important roles in the innate immune response in mammals. However, the expression, molecular properties and immune significances of P2RX7 in lower vertebrates are still very limited. Here we identified and characterized a novel bony fish P2RX7 homologue cDNA, termed poP2RX7, in Japanese flounder (Paralichthys olivaceus). PoP2RX7 protein shares about 60–88% sequence similarity and 45–78% sequence identity with known ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In particular, dominant expression of Japanese flounder P2Y 6 R mRNA transcripts was found in the liver while the least expression was in the spleen ( Figure 3 ). We have shown previously the transcriptional presence of P2X2 , P2X4 , P2X7 , P2Y 2 , and P2Y 12 receptors in various Japanese flounder tissues [ 12 , 18 , 19 , 20 ]. The diversity of purinergic receptor subtypes present in Japanese flounder tissues and cells, addresses an essential role of purinergic receptors in fish through triggering different downstream signaling events.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, dominant expression of Japanese flounder P2Y 6 R mRNA transcripts was found in the liver while the least expression was in the spleen ( Figure 3 ). We have shown previously the transcriptional presence of P2X2 , P2X4 , P2X7 , P2Y 2 , and P2Y 12 receptors in various Japanese flounder tissues [ 12 , 18 , 19 , 20 ]. The diversity of purinergic receptor subtypes present in Japanese flounder tissues and cells, addresses an essential role of purinergic receptors in fish through triggering different downstream signaling events.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that this role is conserved in the Japanese flounder, i.e. activation of poP2X7R can induce an increased gene expression of the proinflammatory cytokines IL-1b and IL-6 in the Japanese flounder head kidney primary cells [15]. Moreover, we have demonstrated the release of ATP by connexin43 and pannexin1 channels in the Japanese flounder immune cells under inflammatory conditions, further supporting the role of extracellular ATP and its associated membrane receptors in fish innate immune response [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…Oocytes were manually defolliculated and incubated 30 min with type III collagenase as previously described . The pIRES‐EGFP/poP2XR7 plasmid was generated as previously described . Oocytes were injected intranuclearly with 4 ng Japanese flounder or rat P2X7R cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterium Edwardsiella tarda was cultured overnight from a single colony with marine LuriaeBertani medium as described in our previous study [19]. The bacterial cultures were then pelleted, washed twice and re-suspended in sterilized physiological saline.…”
Section: Bacterial Infection-induced Ponaca Gene Expressionmentioning
confidence: 99%